Association of CD4(+) CD25(+) T Cells with Prevention of Severe Destructive Arthritis in Borrelia burgdorferi-Vaccinated and Challenged Gamma Interferon-Deficient Mice Treated with Anti-Interleukin-17 Antibody - Nardelli, Dean T. (American Society for Microbiology, 2004)
CD4(+) CD25(+) T cells are a population of regulatory T cells responsible for active suppression of autoimmunity. Specifically, CD4(+) CD25(+) T cells have been shown to prevent insulin-dependent diabetes mellitus, inflammatory bowel disease, and pancreatitis. Here, we present evidence that CD4(+) CD25(+) T cells also play a major role in controlling the severity of arthritis detected in Borrelia burgdorferi-vaccinated gamma interferon-deficient (IFN-γ°) C57BL/6 mice challenged with the Lyme spirochete. When B. burgdorferi-vaccinated and challenged IFN-γ° mice were treated with anti-interleukin-17 (IL-17) antibody, the number of CD4(+) CD25(+) T cells increased in the local lymph nodes. Furthermore, histopathologic examination showed the mice to be free of destructive arthritis. When these anti-IL-17-treated B. burgdorferi-vaccinated and challenged mice were also administered anti-CD25 antibody, the number of CD4(+) CD25(+) T cells in the local lymph nodes decreased. More importantly, severe destructive arthropathy was induced. In addition, delayed administration of anti-CD25 antibody decreased the severity of the arthritis. These results suggest that CD4(+) CD25(+) T cells are involved in regulation of a severe destructive arthritis induced with an experimental model of vaccination and challenge with B. burgdorferi.